Negative Capability: The Psychotherapists' X-Factor? (Existential Analysis: Journal of the Society for Existential Analysis, 2011)
This paper explores role of the therapists' capacity to be in uncertainty in therapeutic practice, drawing on Keats' concept of 'negative capability', and adapting it to describe an aspect of the psychotherapists' process. The paper proposes that the therapists' capacity to be in uncertainty is an important, but previously underrepresented, aspect of practice, because of its elusive nature.
Keywords: Negative capability; uncertainty; Keats; psychotherapy; identity; poetry; unknowing; relationship.